1996
DOI: 10.1063/1.118096
|View full text |Cite
|
Sign up to set email alerts
|

High linear density written transitions in exchange isolated Pt/CoCrTa multilayer thin films

Abstract: Multilayer Pt/CoCrTa thin-film structures have been prepared which display little intergranular exchange coupling and nearly 100% remanence in the perpendicular direction. Magnetic recordings of continuous square wave patterns have been made and characterized using an inductive contact recording transducer and by magnetic force microscopy. Written transitions appear to retain good fidelity at more than 300 000 transitions per inch. With exchange isolation of the grains, media noise becomes negligible relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This is in apparent contrast to recent results we have reported from magnetic recording experiments on films with greater thickness and lower saturation magnetization. 1 The domain wall energy density w decreases with increasing cosputtered CrTa ͑as in A number of shortcomings are apparent in the model employed. The model does not consider hysteresis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in apparent contrast to recent results we have reported from magnetic recording experiments on films with greater thickness and lower saturation magnetization. 1 The domain wall energy density w decreases with increasing cosputtered CrTa ͑as in A number of shortcomings are apparent in the model employed. The model does not consider hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…1 A recent ͑MFM͒ study has shown that equilibrium domain structures vary greatly depending on stoichiometry and deposition temperature. 2 The size of the domain is also strongly influenced by the thickness of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of medium noise in Co/Pt multilayer media [16] was also achieved by using Co-Cr-Ta instead of Co layers with an elevated substrate temperatures [17]. In this case, the reduction in the domain size is caused by the Cr microsegregation in the Co-Cr alloy layer.…”
Section: New Challenges For High Anisotropy Mediamentioning
confidence: 99%
“…Deposition parameters, such as temperature [4] and doping, e.g. B, Cr, CrTa, Al [8][9][10][11][12], have been studied for their potential to reduce domain sizes. Unfortunately, all of these techniques involve high growth temperatures and therefore larger grain sizes.…”
Section: Introductionmentioning
confidence: 99%